COMPARATIVE STUDY OF ISLAMIC LAWS OF WAR AND IHL – POINTS OF CONVERGENCE FOR UNIVERSAL CONSENSUS ON LAWS OF WAR - Syed Mahmood Akhter Hussain Gardezi (Margalla Papers, 2021)
In contemporary times, wars are not taking place in a legal vacuum. There are laws available on resorting to force and conduct of hostilities, including Islamic Laws of war and International Humanitarian Law (IHL). These legal regimes trace their origins in the teaching of elders that have further translated into rules and principles to limit the destructive nature of an armed conflict. Both systems are primarily concerned about regulating the behaviour of belligerents to avoid and at least minimize the sufferings of combatants and non-combatants in the theatre of war. This paper explores Islamic values and rules on the conduct of hostilities and compares them with similar provisions of IHL by using a comparative analysis approach. The objective of this study is not to judge Islamic Laws of war in contrast to IHL or vice versa but addresses the points of convergence. It analyses whether there is any significant difference between these two legal systems in observing principles and ethics of warfare, and provides a way out for humanization.